2021
DOI: 10.3389/fcvm.2021.752763
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnoea in Stanford Type B Aortic Dissection Is Associated With Multiple Imaging Signs Related to Late Aortic Events

Abstract: Background: Obstructive sleep apnoea (OSA) is highly prevalent in patients with Stanford type B aortic dissection (TBAD). Few studies have evaluated the effects of OSA on vascular changes in TBAD patients. This study aimed to explore the effect of OSA on aortic morphological changes in TBAD patients and its relation to late aortic events (LAEs).Methods: This case-control study included 143 TBAD patients. The diameters of different parts of the aorta were measured based on computed tomography angiography (CTA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…63 In addition, a recent study by Zhang et respectively. 61 Another observational study showed that patients with TBAD had a higher apnoea-hypopnea index (17.4 vs. 7.0 events/hr, p = 0.001) and a lower SaO 2 during sleep (average 87% vs. 93%, p = 0.005) when compared with controls. 64 Wang et al 62 attempted to explain how OSA may affect the aorta suggesting that OSA may have both a thrombolytic and a thrombogenesis effect on the FL.…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 97%
See 3 more Smart Citations
“…63 In addition, a recent study by Zhang et respectively. 61 Another observational study showed that patients with TBAD had a higher apnoea-hypopnea index (17.4 vs. 7.0 events/hr, p = 0.001) and a lower SaO 2 during sleep (average 87% vs. 93%, p = 0.005) when compared with controls. 64 Wang et al 62 attempted to explain how OSA may affect the aorta suggesting that OSA may have both a thrombolytic and a thrombogenesis effect on the FL.…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 97%
“…63 In addition, a recent study by Zhang et al showed OSA associated with evident high-risk radiological features in TBAD including aortic diameter ≥40 mm, proximal descending aorta FL diameter ≥22 mm, and a partially thrombosed FL with a risk magnitude of (OR: 4.61, 2.54, 2.56; p < 0.05), respectively. 61 Another observational study showed that patients with TBAD had a higher apnoea–hypopnea index (17.4 vs. 7.0 events/hr, p = 0.001) and a lower SaO 2 during sleep (average 87% vs. 93%, p = 0.005) when compared with controls. 64…”
Section: Population Risk Profilementioning
confidence: 97%
See 2 more Smart Citations